Respuesta :

[tex]( \dfrac{1}{4ab} )^{-2} = (4ab)^2 = 16a^2b^2[/tex]

Answer:

The expression [tex](\frac{1}{4ab})^{-2}[/tex] is [tex]16a^2b^2[/tex]

Step-by-step explanation:

Given :  the expression [tex](\frac{1}{4ab})^{-2}[/tex]

We have to simplify the given expression [tex](\frac{1}{4ab})^{-2}[/tex]

Consider the given expression [tex](\frac{1}{4ab})^{-2}[/tex]

Apply exponent rule [tex]\left(\frac{a}{b}\right)^{-c}=\left(\left(\frac{a}{b}\right)^{-1}\right)^c=\left(\frac{b}{a}\right)^c[/tex]

We have,

[tex]=\left(\frac{4ab}{1}\right)^2=\left(4ab\right)^2[/tex]

Apply exponent rule , [tex]\left(a\cdot \:b\right)^n=a^nb^n[/tex]

[tex]=4^2a^2b^2[/tex]

Simplify, we get,

[tex]=16a^2b^2[/tex]

Thus, The expression [tex](\frac{1}{4ab})^{-2}[/tex] is [tex]16a^2b^2[/tex]